2018
DOI: 10.1183/13993003.01836-2017
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence in the era of severe asthma biologics and thermoplasty

Abstract: Nonadherence to inhaled preventers impairs asthma control. Electronic monitoring devices (EMDs) can objectively measure adherence. Their use has not been reported in difficult asthma patients potentially suitable for novel therapies, i.e. biologics and bronchial thermoplasty.Consecutive patients with difficult asthma were assessed for eligibility for novel therapies. Medication adherence, defined as taking >75% of prescribed doses, was assessed by EMD and compared with standardised clinician assessment over an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 42 publications
3
71
0
7
Order By: Relevance
“…Also highlighted was the significant proportion of patients who feel that their asthma is well controlled when in reality this is not the case, as measured by objective parameters and according to the specialists. A recent study in difficult-to-treat patients who were eligible for biologics reported non-adherence levels close to 60%, in line with previous studies [48].…”
Section: Monitoring Treatment Response and Addressing The Lack Of Adhsupporting
confidence: 86%
“…Also highlighted was the significant proportion of patients who feel that their asthma is well controlled when in reality this is not the case, as measured by objective parameters and according to the specialists. A recent study in difficult-to-treat patients who were eligible for biologics reported non-adherence levels close to 60%, in line with previous studies [48].…”
Section: Monitoring Treatment Response and Addressing The Lack Of Adhsupporting
confidence: 86%
“…Asthma misdiagnosis and poor treatment adherence are relatively common, and may subject patients to unnecessary treatments including OCS . In particular, suboptimal ICS use contributes to poor asthma control, and increases the risk of exacerbations necessitating OCS use or hospitalization .…”
Section: Effective Ocs‐sparing Strategiesmentioning
confidence: 99%
“…Treatment adherence is an important and probably misunderstood behaviour in severe asthma 14 . Despite the frequency of symptoms and the known risk of severe attacks, suboptimal adherence is common in this population, with reported prevalence of suboptimal adherence of 44% in one cohort with severe asthma 15 . Qualitative studies give some insight into this behaviour in severe asthma and the impact of treatment on quality of life.…”
Section: Understanding the Patient's Perspectivementioning
confidence: 99%